Appropriateness of ICNP in Korean home care nursing. Issue 9 (September 2015) - Kang, Min-Jeoung; Kim, Soon-Lae; Lee, Jong-Eun; Jung, Chai Young; Kim, Sukil
Highlights ICNP is not useful as a tool for home care nursing in its present form. Finer granularity of ICNP is needed in home care nursing. Specific concepts to home care nursing need to be added in the focus and action axes. Adding frequent concepts into the focus axis may increase the mapping rate to 90%.